1994
DOI: 10.1073/pnas.91.23.11232
|View full text |Cite
|
Sign up to set email alerts
|

The solubilization of model Alzheimer tangles: reversing the beta-sheet conformation induced by aluminum with silicates.

Abstract: Neurofibrilary tangles are one of two lesions found In the brain ofAl disease victims. With synthetic peptide ents of human neuroflament NF-M17 (Glu-GluLys-Gly-Lys-Ser-Pro-Val-Pro-Lys-Ser-Pro-Val-Glu-Glu-LysGly, pbosphorylated and unphophorlated), CD studies were done to examine the e fect o sodium orthosilicate on the conformatfional state produced by Al+ on faments of neuronal proteins. Previous studies had shown a conformational transiion from a-helix and random to «-pleated sheet upon additionof AP+ to bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

1995
1995
2005
2005

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 28 publications
0
15
0
2
Order By: Relevance
“…The toxic effect of Al has been shown to be reduced in the presence of silicic acid due the formation of hydroxyaluminosilicates. It has been also found that sodiumorthosilicates could reverse Al +3 -induced b-sheet conformation in neurofilament protein (NF-M17) [108]. This has been attributed to the high binding constant of SiO 4 -4 with Al +3 .…”
Section: Al and Other Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The toxic effect of Al has been shown to be reduced in the presence of silicic acid due the formation of hydroxyaluminosilicates. It has been also found that sodiumorthosilicates could reverse Al +3 -induced b-sheet conformation in neurofilament protein (NF-M17) [108]. This has been attributed to the high binding constant of SiO 4 -4 with Al +3 .…”
Section: Al and Other Metalsmentioning
confidence: 99%
“…This has been attributed to the high binding constant of SiO 4 -4 with Al +3 . Based on the contributions, it has been hypothesized that silicates may serve as a possible preventive treatment for individuals showing early symptoms of AD or as a method of retarding the advance of the disease [108]. Thus it seems that metal-metal interrelations play a significant role, but further peer-reviewed data are needed in this area.…”
Section: Al and Other Metalsmentioning
confidence: 99%
“…Over expression of a single NF subunit in transgenic mice has resulted in abnormal accumulation of NF proteins followed by axonal degeneration and hindlimb paralysis of the animals (13). Accumulation of NFs has also been observed in animals exposed to 2,5-hexanedione (14), aluminum (15), IDPN (16), and organophosphate-induced delayed neurotoxicity (OPIDN) (17,18).…”
Section: Introductionmentioning
confidence: 95%
“…The functional groups of the prochelator are then activated by enzymatic or nonenzymatic reactions after they have entered the target organ [121]. Another example is to use simple inorganic silicate that can form very stable complexes with many metals and probably has the ability to enter the BBB [348]. A newly developed copper chelator (tetrathiomolybdate) for Wilson's disease is also suggested as a potential treatment for AD [85,349].…”
Section: ]mentioning
confidence: 99%